Evaluating the socio-economic benefits of the critically endangered african penguin (spheniscus demersus) : a case study of the point colony - Tembe, Skhumbuzo Richard (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2025.